Gestão de TIC no processo de compras públicas: análise da efetividade e dos entraves do sistema SAGUI suprimentos da UFSCar - Ferreira, Fábio Zuccolotto (2022)
The general objective of this work was to evaluate the effectiveness and the obstacles of the System SAGUI Suprimentos of UFSCar, from public procurement processes in the form of price registration. This case study, based on descriptive, exploratory, bibliographic, documentary and qualitative research, analyzed two information systems used at the aforementioned University, one implemented in 2018 and the other in 2021. Direct observation was carried out with field notes in the sector responsible for the IS at the São Carlos Campus from some dimensions and variables considered references by the literature focused on the evaluation of systems implemented in public organizations, such as: ease of use, productivity and time. The study showed that UFSCar's SAGUI Suprimentos system has brought effectiveness to the bidding processes, due to the ease of use, with the new system interface that more clearly presents the images and technical specifications of the products, resembling the well-known "e-commerce"; the productivity dimension, with more concise reports, based on pre-programmed information, which facilitate the grouping of similar items as well as the quantities demanded; by the time dimension, having considerably reduced the duration of the bidding process, despite the constant increase in bureaucracy. The obstacles are more related to the human factor (error) and the unaccompanied demands of users, which are therefore some challenges of the system for greater efficiency and effectiveness in public procurement processes, in addition to the training of users and internal staff.